Pengaruh Kompensasi, Penempatan dan Lingkungan terhadap Kinerja : Semangat Kerja sebagai Pemediasi - Desri Eka Putri (Universitas Putra Indonesia YPTK Padang, 2022)
This study aims to determine the effect of compensation, work placement and work environment on employee performance with work enthusiasm as an intervening variable in the Mentawai Islands Regency Government Environment. The sample in this study was taken by the saturated sample method (census) as many as 95 people. The analytical method used is Structral Equation Modeling (SEM) Analysis with Partial Least Square (PLS). To test the hypothesis, the Path Coefficient is used, which is a test carried out to see the direct effect and the Indirect Effect is a test that aims to see the indirect effect. The results of this study indicate that: 1) Compensation has a positive and insignificant effect on morale, 2) Work placement has a positive and significant effect on morale, 3) Work environment has a positive and significant effect on morale, 4) Compensation has a positive and insignificant effect. on employee performance, 5) Work placement has a positive and insignificant effect on performance, 6) Work environment has a positive and significant effect on performance, 7) Work morale has a positive and significant effect on employee performance, 8) Work enthusiasm mediates compensation on performance, 9) Morale mediates work placement on performance, 10) Morale does not mediate work environment on performance.